2016
DOI: 10.1021/acs.langmuir.6b02983
|View full text |Cite
|
Sign up to set email alerts
|

Centimeter-Scale Surface Interactions Using Hydrodynamic Flow Confinements

Abstract: We present a device and method for selective chemical interactions with immersed substrates at the centimeter-scale. Our implementations enable both, sequential and simultaneous delivery of multiple reagents to a substrate, as well as the creation of gradients of reagents on surfaces. The method is based on localizing submicroliter volumes of liquids on an immersed surface with a microfluidic probe (MFP) using a principle termed hydrodynamic flow confinement (HFC). We here show spatially defined, multiplexed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…The time required for the presentation of the primary antibody to each area of the section was in the range of~30-60 s. This microfluidic approach, allowing a reduction in the incubation times, was enabled by two advantages: (a) only small volumes of liquids are consumed, allowing the concentration of antibodies to be increased without increasing the cost of the assay, and (b) the flow of the antibody solution allows the continuous replenishment of the antibodies consumed from the solution, thereby making the reaction time largely independent of the relatively low diffusion coefficients of the antibodies. Apart from our demonstration of expanding MFP-assisted IHC from the micrometer scale to the centimeter scale, Taylor et al 12 , a related publication by Cors et al 15 additionally showed the integration of dewaxing and rehydration with an MFP to further increase the rapidity of multiplexed IHC staining.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The time required for the presentation of the primary antibody to each area of the section was in the range of~30-60 s. This microfluidic approach, allowing a reduction in the incubation times, was enabled by two advantages: (a) only small volumes of liquids are consumed, allowing the concentration of antibodies to be increased without increasing the cost of the assay, and (b) the flow of the antibody solution allows the continuous replenishment of the antibodies consumed from the solution, thereby making the reaction time largely independent of the relatively low diffusion coefficients of the antibodies. Apart from our demonstration of expanding MFP-assisted IHC from the micrometer scale to the centimeter scale, Taylor et al 12 , a related publication by Cors et al 15 additionally showed the integration of dewaxing and rehydration with an MFP to further increase the rapidity of multiplexed IHC staining.…”
Section: Introductionmentioning
confidence: 74%
“…A versatile and IHC-compatible strategy is to localize antibody solutions in a so-called hydrodynamic flow confinement (HFC) formed at the apex of a noncontact liquid scanning probe, such as a microfluidic probe (MFP) 10 . Multiplexed IHC routines using an MFP were demonstrated by Lovchik et al 7 and Queval et al 11 at the micrometer scale and expanded to the centimeter scale by Taylor et al 12 . Such flow-based approaches were also used for brain slice microenvironment modification 11 and breast cancer sections 12 , as well as in combination with lanthanide-based immunocomplexes 13 and immunofluorescence 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The low reagent consumption demonstrated here using the ESP, shows a prospect for efficient multiplexed patterning of multiple reagents simultaneously. For example, such patterning could be achieved by using an array of adjacent confinements, having a similar geometry to the one used by Taylor et al with pressure driven flow. The main limitations of their system were the relatively high reagent consumption compared even to on‐bench assays, and the high complexity of the fluidic control.…”
Section: Resultsmentioning
confidence: 99%
“…However, we believe this limitation could be addressed by scaling up the dimensions of the MFP and/or by running multiple HFCs in parallel, as previously demonstrated [18]. Also, performing antigen retrieval with the MFP remains elusive as most protocols require temperatures as high as 90°C, whereas paraffin has a softening temperature around 40°C.…”
Section: Discussionmentioning
confidence: 99%